If it's not what You are looking for type in the equation solver your own equation and let us solve it.
8(x-1)=4x+7(8-4x)
We move all terms to the left:
8(x-1)-(4x+7(8-4x))=0
We add all the numbers together, and all the variables
8(x-1)-(4x+7(-4x+8))=0
We multiply parentheses
8x-(4x+7(-4x+8))-8=0
We calculate terms in parentheses: -(4x+7(-4x+8)), so:We get rid of parentheses
4x+7(-4x+8)
We multiply parentheses
4x-28x+56
We add all the numbers together, and all the variables
-24x+56
Back to the equation:
-(-24x+56)
8x+24x-56-8=0
We add all the numbers together, and all the variables
32x-64=0
We move all terms containing x to the left, all other terms to the right
32x=64
x=64/32
x=2
| b.5=13 | | 19c+12=3c+2(6+8c) | | x+6=9/3 | | -.4(3/2x)=9 | | 84=-4(-6x-3) | | x+76x=197x | | 8x+15x+17x=480 | | b-7,b=16 | | x+21=1524 | | 4(p-8)=16 | | 7(w-4)=3w-44 | | -6(1-k)=-2(5-4K) | | 1-5x+7=2x-6 | | H=-49t^2+43t | | 15m=420 | | x.10x–2(x–7)=34 | | -8/3x=2/3 | | x/3=2.4/4 | | 5(w-12)=-80 | | 18/2a=4 | | 4w+4=43 | | x/(-12)=-9 | | -3(-1+p)-5(p-7)=14 | | n/15=9/5 | | −2+4/5x=6 | | 70=1.4t | | X^2+2x-5=3x^2-4x+1 | | 8x–15x=-44-12 | | -8w=-2 | | -12=-32×4x | | -8v+5(v-4)=7 | | 4/x=2.4/1.6 |